Abnormal amygdala resting-state functional connectivity in primary dysmenorrhea. Issue 5 (20th March 2019) - Shen, Zhifu; Yu, Siyi; Wang, Minyu; She, Tianwei; Yang, Ya; Wang, Yanan; Wei, Wei; Guo, Xiaoli; Hu, Youping; Liang, Fanrong; Yang, Jie
Abstract : Neuroimaging studies have manifested functional abnormalities in pain-related brain regions in patients with primary dysmenorrhea (PDM). However, as the key region in brain pain matrix, whether and how the amygdala functional network alteration in PDM is unclear. In this study, we aimed to investigate the intrinsic amygdala functional connectivity (AFC) network alteration in patients with PDM during ovulatory period. Thirty-six PDM patients and 35 matched healthy controls were enrolled in this study. The AFC was constructed using amygdala-based functional connectivity using resting-state functional MRI data. The plasma prostaglandin E2 level was measured during ovulatory period. The group difference on AFC network was conducted and further explored the clinical significant of the abnormal AFC network in PDM patients. Compared to the healthy control group, PDM patients showed increased left AFC in default mode network, including medial prefrontal cortex, posterior cingulate cortex/precuneus, angular gyrus, and inferior temporal gyrus, while, decreased left AFC at bilateral nucleus accumbens/orbital frontal cortex, and decreased right AFC network in right orbital frontal cortex and insula, ventral tegmental area (VTA), left hippocampal, and insula. In addition, the decreased right AFC in VTA was associated with higher plasma prostaglandin E2 level in the PDM group. The AFC network was disrupted in PDM patients, mainly in default mode network and reward system. The disrupted connectivity between amygdala and VTA might contribute to the prostaglandins associated pathological mechanism of PDM.